A personalized molecular approach in multiple myeloma: the possible use of RAF/RAS/MEK/ERK and BCL-2 inhibitors - Vincenzo Raimondi; Nicolas Thomas Iannozzi; Jessica Burroughs-Garcìa; Denise Toscani; Paola Storti; Nicola Giuliani (Open Exploration Publishing Inc., 2022)
Multiple myeloma (MM) is a blood cancer that derives from plasma cells (PCs), which will accumulate in the bone marrow (BM). Over time, several drugs have been developed to treat this disease that is still uncurable. The therapies used to treat the disease target immune activity, inhibit proteasome activity, and involve the use of monoclonal antibodies. However, MM is a highly heterogeneous disease, in fact, there are several mutations in signaling pathways that are particularly important for MM cell biology and that are possible therapeutic targets. Indeed, some studies suggest that MM is driven by mutations within the rat sarcoma virus (RAS) signaling cascade, which regulates cell survival and proliferation. The RAS/proto-oncogene, serine/threonine kinase (RAF)/mitogen-activated extracellular signal-regulated kinase (ERK) kinase (MEK)/ERK signaling pathway is deregulated in several cancers, for which drugs have been developed to inhibit these pathways. In addition to the signaling pathways, the disease implements mechanisms to ensure the survival and consequently a high replicative capacity. This strategy consists in the deregulation of apoptosis. In particular, some cases of MM show overexpression of anti-apoptotic proteins belonging to the B cell lymphoma 2 (BCL-2) family that represent a possible druggable target. Venetoclax is an anti-BCL-2 molecule used in hematological malignancies that may be used in selected MM patients based on their molecular profile. We focused on the possible effects in MM of off-label drugs that are currently used for other cancers with the same molecular characteristics. Their use, combined with the current treatments, could be a good strategy against MM.